Regional Economic Outlook, November 2018, Middle East and Central Asia. (Regional Economic Outlook, 2018)
As in other regions in the world, countries in MENAP and CCA regions are exposed to tightening in global financing conditions and ongoing global trade tensions. The former has already begun to impact several emerging market economies in MENAP and could have more severe implications should financial market sentiment suddenly deteriorate. Escalating global trade tensions will have a limited direct and immediate impact on these regions but could impart significant strains over time through negative effects on trading partners and through market confidence effects.